Verdade e justiça ao meio-dia: a construção da experiência moral num programa de TV - Veloso, Wanessa Souto (2013)
This work is based on a case study: a policial news TV program produced in João Pessoa. This show is well known for its shocking and violent images and its presenter is also a kind of local celebrity for his role. This TV show elaborates ideas of necessary truth‟ and justice‟ supposedly not guaranteed by the government. In this way, it intends to recreate media as a kind of public space where justice requests are solved. Based on a participant observation, the research aims to understand the news elaboration and, particularly, how the public connects with the presenter and his conceptions of justice.